Functional Interfaces, Biological Pathways, and Regulations of Interferon-Related DNA Damage Resistance Signature (IRDS) Genes - Padariya, Monikaben; Sznarkowska, Alicja; Kote, Sachin; Gómez-Herranz, Maria; Mikac, Sara; Pilch, Magdalena; Alfaro, Javier; Fahraeus, Robin; Hupp, Ted; Kalathiya, Umesh (Biomolecules, 2021)
Interferon (IFN)-related DNA damage resistant signature (IRDS) genes are a subgroup of interferon-stimulated genes (ISGs) found upregulated in different cancer types, which promotes resistance to DNA damaging chemotherapy and radiotherapy. Along with briefly discussing IFNs and signalling in this review, we highlighted how different IRDS genes are affected by viruses. On the contrary, different strategies adopted to suppress a set of IRDS genes (STAT1, IRF7, OAS family, and BST2) to induce (chemo- and radiotherapy) sensitivity were deliberated. Significant biological pathways that comprise these genes were classified, along with their frequently associated genes (IFIT1/3, IFITM1, IRF7, ISG15, MX1/2 and OAS1/3/L). Major upstream regulators from the IRDS genes were identified, and different IFN types regulating these genes were outlined. Functional interfaces of IRDS proteins with DNA/RNA/ATP/GTP/NADP biomolecules featured a well-defined pharmacophore model for STAT1/IRF7-dsDNA and OAS1/OAS3/IFIH1-dsRNA complexes, as well as for the genes binding to GDP or NADP+. The Lys amino acid was found commonly interacting with the ATP phosphate group from OAS1/EIF2AK2/IFIH1 genes. Considering the premise that targeting IRDS genes mediated resistance offers an efficient strategy to resensitize tumour cells and enhances the outcome of anti-cancer treatment, this review can add some novel insights to the field.
Keywords: Drug Resistance, Neoplasm; DNA Damage; transkripční faktor STAT1; Cell Line, Tumor; Adaptor Proteins, Signal Transducing; RNA, Double-Stranded; adaptorové proteiny signální transdukční; dvouvláknová RNA; proteiny vázající RNA; interferonový regulační faktor 7; lidé; chemorezistence; intracelulární signální peptidy a proteiny; signální transdukce; Signal Transduction; poškození DNA; Interferon Regulatory Factor-7; STAT1 Transcription Factor; Intracellular Signaling Peptides and Proteins; aktivace transkripce; interferony; RNA-Binding Proteins; Interferons; Transcriptional Activation; nádorové buněčné linie; Humans